Analisis Determinan Terhadap Penghindaran Pajak Pada Perusahaan Makanan Dan Minuman - januri januri (Jurnal Riset AKuntansi dan Bisnis, 2020)
Hypothesis Test, Determinant Test.The results showed that partially corporate social responsibility had no effect on tax avoidance at food and beverage companies, capital intensity partially had no effect on tax avoidance at food and beverage companies, partial leverage had no effect on tax avoidance and corporate social responsibility, capital intensity. and Leverage simultaneously affects Tax Avoidance at Food and Beverage Companies Listed on the IDX for the 2015-2018 period with an R Square value of 0.404 or 40.4%, which means that the variation of Tax Avoidance with Corporate Social Responsibility, Capital Intensity and Leverage while the rest 59.6% of other variables not examined by this study, for example Profitability, company size, Inventory Intensity and Company Characteristics.